Solve this equation.
5x-2y=3
y=2x
1 answer:
Answer:
3
Step-by-step explanation:
5x-2y=3 when: y=2x
1. Plug in the y-value (y=2x) into the equation (5x-2y=3). The equation should then look like 5x-2(2x)=3
2. Simplify:
5x-2(2x)=3
5x-4x=3
1x=3
x=3
Check:
5x-2(2x)=3 (plug in the x-value you solved for: 3)
5(3)-2×2(3)=3
15-2×6=3
15-12=3
3=3
Hope this helped !
Cheers, Z
You might be interested in
For a direct variation, f(x) = kx. Therefore, for f(x) = 30x, constant of variation (k) = 30.
Hello There!
(15 x 2) + (8 x 2) = 46
Answer: A. 46 feet.
Hope This Helps You!
Good Luck :)
- Hannah ❤
Answer:
34
Step-by-step explanation:
that what i think
Answer:
EXPLAIN
Step-by-step explanation:EXPLAIN
EXAMPLE